2018
DOI: 10.1042/bcj20170857
|View full text |Cite
|
Sign up to set email alerts
|

Globular C1q receptor (p33) binds and stabilizes pro-inflammatory MCP-1: a novel mechanism for regulation of MCP-1 production and function

Abstract: The protein gC1qR (globular C1q receptor), also named p33, was originally identified as a binding partner of the globular heads of C1q in the complement system. gC1qR/p33 is abundantly expressed in many cell types, but the functional importance of this protein is not completely understood. Here, we investigate the impact of gC1qR/p33 on the production and function of the pathophysiologically important chemokine monocyte chemoattractant protein-1 (MCP-1) and the underlying molecular mechanisms. Knockdown of gC1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Anders et al. ( 16 ) found that the globular C1q receptor (p33), a binding partner of C1q in the complement system, could stabilize CCL2 protein. In vitro studies have revealed high-affinity binding between CCL2 protein and p33, and recombinant p33 greatly enhanced CCL2 persistence and the migration capacity of THP-1 monocytes.…”
Section: Regulation Of Ccl2 Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anders et al. ( 16 ) found that the globular C1q receptor (p33), a binding partner of C1q in the complement system, could stabilize CCL2 protein. In vitro studies have revealed high-affinity binding between CCL2 protein and p33, and recombinant p33 greatly enhanced CCL2 persistence and the migration capacity of THP-1 monocytes.…”
Section: Regulation Of Ccl2 Productionmentioning
confidence: 99%
“…In recent years, many non-canonical factors have been reported to directly bind to the cis-element of the CCL2 gene or protein independent of classical pathways. Anders et al (16) found that the globular C1q receptor (p33), a binding partner of C1q in the complement system, could stabilize CCL2 protein. In vitro studies have revealed high-affinity binding between CCL2 protein and p33, and recombinant p33 greatly enhanced CCL2 persistence and the migration capacity of THP-1 monocytes.…”
Section: Regulation Of Ccl2 Productionmentioning
confidence: 99%
“…Previous studies in peripheral cell types suggested its role in the regulation of oxidative phosphorylation, and also the regulation of mitochondrial gene expression either as a chaperone or as a transcription factor 17,24,32 . Among the many previously suggested functions of C1qbp, these mitochondrial functions but not immunosignalling of surface C1qbp 6,8,58 and cytosolic/nuclear mRNA chaperone functions 17,18 are likely based on its subcellular distribution in brain cells.…”
Section: Discussionmentioning
confidence: 96%
“…C1qbp (gC1qR) has been implicated in the modulation of the immune response to pathogens 5 . Different mechanisms have been proposed including the pro-inflammatory role of C1qbp (gC1qR) by promoting the migration of macrophages 6,7 , and the mediation of the actions of pro-inflammatory agents, such as high molecular weight kininogen to produce further pro-inflammatory agents 5,8 . C1qbp can also prevent cell damage by the elimination of C1q, and other ligands including antimicrobial peptides from the inflammatory site 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…MCP-1 acts as a monocyte chemotactic protein, mainly secreted by monocytes, macrophages and dendritic cells (Anders et al 2018;Du et al 2016). When an inflammatory reaction occurs, it activates the chemotaxis of monocytes/macrophages, activates the expression of leukocyte adhesion molecule-1, induces the production of the cytokine IL-1, IL-6, and regulates expression of specific adhesion molecules such as CDllc and CDllb on the surface of monocyte (Anders et al 2018;Du et al 2016). Besides, as an important inflammatory initiating factor, TNF-α has the cytotoxic and multiproinflammatory effects, indicating the activation of inflammatory (Zhang et al 2011).…”
Section: Discussionmentioning
confidence: 99%